Reciprocal TCR-CD3 and CD4 Engagement of a Nucleating pMHCII Stabilizes a Functional Receptor Macrocomplex - Glassman, Caleb R. (Cell Rep, 2018)
CD4(+) T cells convert the time that T cell receptors (TCRs) interact with peptides embedded within class II major histocompatibility complex molecules (pMHCII) into signals that direct cell-fate decisions. In principle, TCRs relay information to intracellular signaling motifs of the associated CD3 subunits, while CD4 recruits the kinase Lck to those motifs upon coincident detection of pMHCII. But the mechanics by which this occurs remain enigmatic. In one model, the TCR and CD4 bind pMHCII independently, while in another, CD4 interacts with a composite surface formed by the TCR-CD3 complex bound to pMHCII. Here, we report that the duration of TCR-pMHCII interactions impact CD4 binding to MHCII. In turn, CD4 increases TCR confinement to pMHCII via reciprocal interactions involving membrane distal and proximal CD4 ectodomains. The data suggest that a precisely assembled macrocomplex functions to reliably convert TCR-pMHCII confinement into reproducible signals that orchestrate adaptive immunity.